Calcium Channel Blocker Versus Renin–Angiotensin System Inhibitor in Risk of Kidney Cancer Among Patients With Hypertension: A Propensity Score‐Matched Cohort Study - Minji Jung; Shufeng Li; Zhengyi Deng; Jinhui Li; Mingyi Li; Satvir Basran; Marvin E. Langston; Benjamin I. Chung (Cancer Medicine, 2024)
ABSTRACT Background Use of antihypertensive medications could be associated with an increased risk of kidney cancer. Despite their various mechanisms of action, whether this association differs between different classes of medications remains unclear. Objective The objective of this study is to compare the risk of kidney cancer between first‐line treatment options of antihypertensive medications in a hypertensive population. Method In this retrospective cohort study, we used the MarketScan Databases (2007–2021). We included individuals older than 30 years of age with a diagnosis of hypertension who received first‐line medications for hypertension, which included three classes: angiotensin‐converting enzyme inhibitors (ACEI), angiotensin receptor blockers (ARB), and dihydropyridine calcium channel blockers (dCCB). We applied a propensity score matching method and created three separate cohorts: (1) ARB versus ACEI, (2) dCCB versus ACEI, and (3) dCCB versus ACEI. For non‐dCCB, we repeated the analyses. The primary outcome was kidney cancer incidence. To assess kidney cancer risk, we applied multivariable conditional Cox proportional hazards models. Results In the first cohort, ARB use was associated with an increased risk of kidney cancer compared to ACEI use (hazard ratio [HR] 1.10, 95% confidence interval [CI] 1.02–1.18). In the second cohort, dCCB use was associated with an increased risk of kidney cancer compared to ACEI use (HR 1.29, 95% CI 1.18–1.40). In the third cohort, dCCB use was associated with a higher risk of kidney cancer compared to ARB use (HR 1.17, 95% CI 1.08–1.28). Null association was shown when comparing non‐dCCB with ACEI or ARB use. Conclusion Use of dCCB showed a higher risk of kidney cancer compared to ACEI or ARB use in patients with hypertension.